Analisis Perkembangan Bahasa Semantik Dan Sintaksis Anak Dalam Kegiatan Belajar Dari Rumah - Nikmatul Azizah; Anita Candra Dewi (UIN Sultan Maulana Hasanudin Banten, 2021)
Language is a very important communication tool for every human being. The older the child, the more and more vocabulary development will be. Aspects that make up language include semantics and syntax. During the COVID-19 pandemic, children's semantic and syntactic language development was not well monitored, because learning was carried out remotely or Learning From Home (BDR). Parents have difficulty accompanying children to learn from home and sometimes children are less interested in doing activities because learning is not interesting so parents do not send documentation of children's learning at home. The purpose of this study was to determine the development of children's semantic and syntactic language through Learning From Home activities. This study uses the method of observation conducted on 2 children aged 4-5 years with different sexes. Observations were made by observing the documentation of children's learning from home through storytelling strategies with videos, conversing with video calls and playing video cards with letter and word cards. Based on the observations, this strategy is effective for improving children's semantic and syntactic language skills.